Privacy Protection of Juvenile in Conflict with the Law at the Trial - Kvrivishvili, Tatia (Journal of Law, 2019)
The present article refers to the issue of privacy of the juvenile in conflict with the law, in particular the rule of examination of the case in closed court hearings and the issue of restriction of attendees at the trial; What are the international standards in this regard, the practice of foreign countries and legislative regulation in Georgia. There is a separate chapter on the controversy surrounding two competitive rights: the right to a privacy of the juvenile and the right to a public hearing, reviewing case-law of the European Court of Human Rights and the Courts of Foreign Countries. As the juvenile justice code of Georgia has strictly defined the procedure of considering the juvenile case behind closed doors without any exeption and restricted by the list of attendees, it will be analyzed on the basis of international practice research, whether this provision is always in the best interest of the juvenile and protects the juveniles' rights.